2016
DOI: 10.1177/0969776416637208
|View full text |Cite
|
Sign up to set email alerts
|

Staging a ‘Chinatown’ in Berlin: The role of city branding in the urban governance of ethnic diversity

Abstract: Migration is predominantly directed towards cities that have been facing a highly competitive global environment within the last 30 years of globalisation. Against the background of economic restructuring, cities are looking for new forms of city branding. In this process, ethno-cultural diversity is increasingly regarded as an asset, leading to the branding of migrant neighbourhoods, especially those characterised by migrant economies. These agglomerations of shops, cafés and restaurants provide places of lei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Lack of public engagement -Effective placemaking requires active public participation and engagement (Galanakis 2013;Karacor 2014;Schmiz 2016;Rath et al 2017;Schmiz & Kitzmann 2017). Ethnic entrepreneurs' experiences of a retail space largely depend on the extent to which they participated in the placemaking process.…”
Section: Ethnic Entrepreneurs In Suburban Placemakingmentioning
confidence: 99%
“…Lack of public engagement -Effective placemaking requires active public participation and engagement (Galanakis 2013;Karacor 2014;Schmiz 2016;Rath et al 2017;Schmiz & Kitzmann 2017). Ethnic entrepreneurs' experiences of a retail space largely depend on the extent to which they participated in the placemaking process.…”
Section: Ethnic Entrepreneurs In Suburban Placemakingmentioning
confidence: 99%
“…This argument highlights the need for a spatially sensitive approach in different urban settings. As research has shown, a relational perspective to space (Massey ) as applied by Glick Schiller and Çağlar () may help to conceptualise the scalar positioning of a city, its specific migration history and its embeddedness into broader financial and economic power structures as well as migrant transnational networks (Schmiz ; Räeuchle & Schmiz ). In drawing on this argument, Räuchle & Nuissl and Schmiz (this issue) show that the symbolic value of ethnic economies has led to this new field of political engagement in branding.…”
Section: The Symbolic Value Of Ethnic Entrepreneurshipmentioning
confidence: 99%
“…Within this literature, migrant entrepreneurs are addressed as placemakers with a high social value for the ethnic community (Wood 1997;Bergmann 2011;Haid 2013;Kaplan 2015;Ülker 2016). This has been demonstrated, for example, for retail in Parisian neighbourhoods (Kaplan 2015), a Vietnamese wholesale centre in Berlin (Schmiz 2017), themed Chinese shopping malls in Toronto (Zhuang 2008) and an informal Thai food market in Berlin's Preußenpark (Haid 2013). In terms of economic placemaking, Stock (2013) shows the creative practices of falafel snack bar owners and how their strategic reaction to changing customer tastes makes them symbolic markers in gentrification processes in Berlin.…”
Section: Placemaking and Social Inclusionmentioning
confidence: 99%
“…During the Cold War, the downtown district named Mitte (meaning "middle" in English) was converted into prohibited military zones filled with desolation and horror after the construction of the Berlin Wall ( Figure 1). After reunification in 1989, the formerly desolated Mitte was massively invested in and drastically reconstructed, generating great demand for manual labor [40]. Due to the previously signed recruitment agreement, most of the Turkish immigrants, especially the less educated and low skilled, agglomerated in Mitte for construction jobs [4].…”
Section: Case Study Area: Mitte Berlinmentioning
confidence: 99%